Superior ethanol-sensing behavior based on SnO2 mesocrystals incorporating orthorhombic and tetragonal phases. Issue 12 (11th February 2015) - Gu, C. D.; Zheng, H.; Wang, X. L.; Tu, J. P.
<x xml:space="preserve">Abstract</x> Nanoporous SnO2 mesocrystal with mixed tetragonal and orthorhombic phases and superior ethanol-sensing performance is synthesized via a facile annealing topotactic transformation from the ionothermal synthesized SnO precursor under ambient-pressure.